AXLOQ VA UNING JAMIYAT HAYOTIDAGI OʻRNI - Djamilova, G.J.; Joldasbayev, O.Y. (SCIENCE and SOCIETY, 2025)
The article examines the role and importance of ethics in human life and the education of youth. Morality is the basis of human relations with society. In the education of youth, it is said about the need to develop such qualities as respect for society and humane attitude towards people, as well as activities based on Eastern and national moral standards.